An Analysis of Expressive Speech Acts in Engene Comments on Enhypen’s Weverse - Kharisma, Dewi; Rusmana, Dadan; Budiarti, Dian (Journal of English Language and Education, 2025)
This research evaluates the expressive speech acts employed by Engene in their comments on Enhypen’s Weverse platform posts, focusing on the role of these speech acts in fan-idol interactions. Using a qualitative descriptive approach with a pragmatic perspective, the study examines selected textual comments from Engene, classifying and identifying the speech acts embedded in their words and expressions. The analysis centers on how these speech acts function within social interactions, particularly in fostering emotional connections between fans and idols. The study identifies five main types of expressive speech acts present in Engene’s comments: admiration, encouragement, gratitude, celebration, and expressions of sadness or regret. Among these, admiration is the most prevalent, reflecting the deep emotional bond fans establish with Enhypen. Encouragement serves as a means for fans to motivate and support their idols, while gratitude expresses appreciation for Enhypen’s efforts and impact. Celebration often appears in response to achievements or significant moments, reinforcing the shared joy between fans and idols. Conversely, expressions of sadness or regret emerge when fans resonate with emotional or difficult experiences shared by Enhypen. By analyzing these speech acts, the study highlights how fan discourse on Weverse extends beyond simple interactions, shaping the dynamics of parasocial relationships and reinforcing the idol-fan connection. This research underscores the significance of language in digital fan communities, demonstrating how expressive speech acts create a sense of closeness, emotional investment, and mutual engagement between Engene and Enhypen within the Weverse platform.